MECHANISM OF PUBLIC ADMINISTRATION FOR ENSURING QUALITY AND SAFETY OF LIFE - Hlubitskyi, Oleh (Public Management and Policy, 2025)
The article focuses on exploring public administration mechanisms aimed at maintaining a high level of quality and safety of life for the population amid current challenges in Ukraine. The purpose of the study is to analyze the public administration mechanisms implemented by state institutions to improve the level of security and quality of life of citizens in response to socioeconomic and political changes. The study employed general scientific methods of cognition: analysis, synthesis, induction, deduction, generalization, a systems approach, and comparative analysis. The research findings indicate that public administration mechanisms in Ukraine have a complex and multi-level structure that involves the activities of higher state authorities and local self-government bodies. It is concluded that these institutions implement state policy through strategic planning, legislative activities, control, and administrative regulation. The study shows that the President of Ukraine, the Verkhovna Rada, the Cabinet of Ministers, as well as other central executive bodies, are engaged in developing regulatory legal acts, ensuring law enforcement, and protecting citizens’ rights and freedoms while maintaining public order and the country’s defense capability. The study also highlights the importance of administrative and service functions, such as the issuance of permits, licenses, and other services that directly influence the regulation of life safety standards. Additionally, indexes of quality of life and safety are analyzed to reflect the changing living conditions of the population in modern Ukraine. It is concluded that the current political situation, ongoing military actions, and economic transformations have a significant impact on the indicators of quality of life. The study shows that public authorities focus their efforts on stabilizing and improving living standards, which is critically important for building public trust, maintaining social stability, and increasing the efficiency of management processes under crisis conditions. The practical value of the study lies in the possibility of using its results to improve public administration strategies aimed at strengthening social security and enhancing the quality of life of citizens.